Uterine cancer in Lima - Ruiz Rolando, Ernesto (1920)
The cancer problem is interesting topic because of the number of issues raised, although their study was limited to the features offered in a given locality and in an organ of the economy, in particular. In this study we limit ourselves only to the critical appraisal of uterine cancer mortality determined in Lima and outline the actions to be taken to halt and if possible, reduce the high coefficients provided as a result of the delay in diagnosis.